Over-the-counter and prescription medications for acne: A cross-sectional survey in a sample of university students in Saudi Arabia - Mohja D Alshehri; Abdulsalam T Almutairi; Asma M Alomran; Batool A Alrashed; Feroze Kaliyadan (Wolters Kluwer Medknow Publications, 2017)
Introduction and Background: Acne is a very common dermatological condition found among the adolescent population in Saudi Arabia. Many patients with acne try various forms of self-medication, over the counter medicines (OTC), and prescription medicines for the same. Materials and Methods: This was a cross-sectional study among university students in the Kingdom of Saudi Arabia (KSA). A validated questionnaire was distributed to a convenience sample of university students to evaluate their knowledge and attitudes towards OTC (mainly) as well as prescription medicine for acne. Chi-square and multiple logistic regression tests were used for comparisons between groups. Results: Four hundred and twenty valid, completed questionnaires were obtained. A total of 220 (52.4%) used some type of OTC medications at least once, where as 108 (25.7%) used prescription medicines and 92 (21.9%) used both. The most common OTC medications used were cleansers by 250 participants (41.9%). Among prescription medicines, the most common were topical and oral antibiotics (11.4%). Bivariate and multivariate analysis showed that females are statistically more likely to use OTC medicines compared to males (Odds ratio: 1.7). Conclusion: The use of self-medications and OTC medications is common among university students in KSA. The most common OTC medicine used for acne was cleanser.